Seed mass and aeed yield of six roses (Rosa L., Rosacear Adans.) from c entral russia (Republic of Mordovia) - Khapugin, Anatoliy A. (Plant Breeding and Seed Science, 2015)
Genus Rosa L. is one of most critical taxa within European flora. Majority works is devoted to phylogeny, taxonomy and nomenclature of roses. Investigations of morphology and ecology of roses are still relatively few in number. The aim of this study was to evaluate seed mass and seed yield of six rose species (Rosa cinnamomea, R. spinosissima, R. rugosa, R. rubiginosa, R. glauca and R. canina) from populations in Central Russia (Republic of Mordovia). As a result of the study, it was revealed that Rosa rugosa has maximal number of seeds per rosehip among all investigated roses. Roses from section Caninae are characterized by large number of achenes per rosehip too. In contrast, among all investigated species, Rosa cinnamomea have most minimal seed yield. Origin of Rosa spinosissima population in Ruzaevka district (Republic of Mordovia, Central Russia) was proposed as uncertain according to number of seeds per rosehip. At first time, the seed mass of Rosa cinnamomea, R. glauca and R. rubiginosa was revealed.